Evaluation of Ir and Pd(NO3)2/Mg(NO3) 2 as modifiers for the simultaneous determination of Mn, Ni, Pb, and Sb in fuel ethanol by graphite furnace AAS - Neves, Denise Regina [UNESP]; Oliveira, Silvana Ruella [UNESP]; Rêgo, Jardes Figuerêdo Do [UNESP]; Flumignan, Ddjkilo Luiz [UNESP]; Oliveira, José Eduardo [UNESP]; Neto, José Anchieta Gomes [UNESP] (My University, 2010)
The mixture Pd(NO3)2/ Mg(NO3)2 and an Ir-coated platform co-injected with Pd(NO3)2/ Mg(NO3)2 were evaluated as modifiers for the direct and simultaneous determination of Mn, Ni, Pb, and Sb in fuel ethanol by graphite furnace atomic absorption spectrometry. For a 20-μL diluted sample dispensed onto the platform of graphite tube in the presence of 5 μg Pd and 3 μg Mg, analytical curves in the 0 - 50.0 Mg L-1 range were built up resulting in linear correlation coefficients better than 0.99. The calculated characteristic masses were 6 pg Mn, 25 pg Ni, 67 pg Pb, and 50 pg Sb. The limits of detection (LOD) were 0.13 Mg L' Mn, 1.2 pg L-1 Ni, 1.2 Mg L' Pb, and 0.10 Mg L-1 Sb. Accuracy was checked after the analysis of 10 commercial fuel ethanol samples. The results were in agreement at a 95% confidence level (paired Mest) with those obtained by inductively coupled plasma mass spectrometry. The recovery of Mn, Ni, Pb, and Sb in fuel ethanol samples was within the 97-104%, 86-116%, 83-119%, and 92-104% intervals, respectively, and the relative standard deviation (n = 12) was typically 4%, 7%, 6%, and 5%, respectively. The useful lifetime of the THGA atomizer was around 300 firings.